Tinjauan Literatur Formulasi Sabun Cuci Piring Cair Berbasis Ekstrak Jeruk Nipis (Citrus aurantifolia) sebagai Pelarut Lemak Alami - Aqil Rahmatul Fiqram; Nurfadila Islami; Nursa’ada; Ramlawati; Sahrani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Synthetic-based dish soaps are widely used in household activities but have the potential to cause negative impacts on the environment and skin health due to the use of chemical surfactants. Safer, more environmentally friendly alternatives are needed by utilizing natural ingredients such as lime (Citrus aurantifolia), which contains active compounds limonene, flavonoids, and citric acid as natural fat solvents. This study aims to analyze and synthesize various research findings regarding the formulation of liquid dish soap based on lime extract, including its effectiveness in fat dissolution and physical product characteristics. The method used is a Systematic Literature Review (SLR) with literature searches through Google Scholar and ScienceDirect databases covering the 2020–2026 period, yielding 20 relevant articles that were analyzed descriptively and comparatively. The results show that the optimal concentration of lime extract (10%) produces a suitable pH and the best cleaning power. Limonene content has been shown to improve emulsion stability and accelerate fat degradation, while the cold saponification method is better able to maintain natural bioactive compounds compared to the hot method. The type of vegetable oil (moringa oil, VCO, olive oil) and the balanced concentration of NaOH/KOH also significantly affect soap quality. Furthermore, the utilization of waste cooking oil as a raw material supports the circular economy and reduces environmental impact by up to 80%. In conclusion, liquid dish soap formulations based on lime extract have great potential as effective, safe, and sustainable cleaning products. Further research is needed, including field-scale tests, long-term stability tests, skin irritation tests, and life cycle assessment (LCA) analysis to support product commercialization.